The European Accreditation of Istituto Tumori Giovanni Paolo II of Bari. (December 2015) - Lacalamita, Rosanna; Quaranta, Antonio; Trisorio Liuzzi, Maria Pia; Nigro, Aldo; Simonetti, Umberto; Schirone, Massimiliano; Aloè, Ferruccio; Capochiani, Gianluca; De Francesco, Genoveffa; Gadaleta, Cosimo; Galetta, Domenico; Grammatica, Luciano; et al.
The National Cancer Institute of Bari (Istituto di Ricovero e Cura a Carattere Scientifico, IRCCS) has been involved since the conception of the project of the Italian Ministry for Health aimed to validate the applicability of the Organisation of European Cancer Institutes (OECI) accreditation and designation (A&D) model to the Network of Italian Cancer Centers, IRCCS, of Alleanza Contro il Cancro. The self-assessment phase of the Institute started in September 2013 and ended in June 2014. All documents and tools were transferred to the OECI A&D Board in June 2014 and a 2-day peer review visit was conducted in October 2014 by an international qualified audit team. The Institute received its final designation and certification in June 2015. The OECI A&D Board, in its final report, came to the conclusion that Istituto Tumori "Giovanni Paolo II" of Bari has a strong research component with some essential elements of comprehensive cancer care still under development; the lack of a system for using outcome data for the strategic management approach to decision-making and missing a regular internal audit system eventually helping further quality improvement were reported as examples of areas with opportunities for improvement. The OECI A&D process represented a great opportunity for the cancer center to benchmark the quality of its performance according to standard parameters in comparison with other international centers and to further develop a participatory group identity. The common goal of accreditation was real and participatory with long-lasting positive effects. We agree with the OECI comments about the next areas of work in which the Institute could produce future further efforts: the use of its powerful IT system as a means for outcome analysis and empowerment projects for its cancer patients.